2020
DOI: 10.1371/journal.pone.0231340
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of domestic decision-making power and social support as predictors of postpartum depressive and physical symptoms between immigrant and native-born women

Abstract: Background Women's participation in decision-making in the household is an indicator of women's empowerment. Few studies have compared domestic decision-making power and its effect on postpartum health between immigrant and native-born women. This study aimed to examine the effect of domestic decision-making power and social support during pregnancy on predicting postpartum depressive and physical symptoms among immigrant and nativeborn mothers in Taiwan. Methods and findings This prospective study recruited 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 17 publications
1
21
0
1
Order By: Relevance
“…They demonstrated that women characterized by lower domestic-decision-making power and social support during pregnancy were more commonly diagnosed with postpartum depression. Similar results were obtained in women working full-time and with lower family income [ 37 ]. The authors suggested that the population of immigrants was healthier and more motivated, so depression occurred less frequently than in the local population.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…They demonstrated that women characterized by lower domestic-decision-making power and social support during pregnancy were more commonly diagnosed with postpartum depression. Similar results were obtained in women working full-time and with lower family income [ 37 ]. The authors suggested that the population of immigrants was healthier and more motivated, so depression occurred less frequently than in the local population.…”
Section: Discussionsupporting
confidence: 84%
“…The risk increased due to preterm delivery, delayed initiation of breastfeeding and lower birth weight of the child. A retrospective study by Chen et al demonstrated that the risk of postpartum depression was 3-fold higher in women who experienced preeclampsia intragestationally, whilst in case of severe preeclampsia, the risk was even 4-fold [ 37 ]. Similarly, pregestational obesity also indirectly correlated with the risk of PPD, probably due to the obesity-induced stress mechanism [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…While risk factors, such as not having a partner [ 10 , 11 ], lower social support [ 12 , 13 , 14 ], lower partner satisfaction [ 15 , 16 , 17 ], and multiparity [ 18 ] for perinatal depression have been identified, their associations with PAS have yet to be determined among perinatal women living in Mexico. Cesarean delivery and stressful life events [ 18 , 19 , 20 , 21 ] are risk factors for PAS in Colombia, Australia, and Rwanda, while resilience has been identified as a protective factor for PAS [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Chen et al reported no increased risk of postpartum depression associated with the mode of delivery or neonatal status in patients with pre-eclampsia, during pregnancy. However, the researchers noted a 3- to 4-fold increase of the risk associated with the primary disease [ 22 ].…”
Section: Discussionmentioning
confidence: 99%